Basic Thinking Skills Included in the science curriculum’s content for the first and second grades of basic education in the Syrian Arab Republic - زمرد, أميرة; يوسف, سمر; عيسى, مدار (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This Research aimed to determine the degree to which Basic Thinking Skills are included in Science curriculum’s content for the first and Second Grades. To achieve this goal, a list of The Basic Thinking Skills that are included in the content of these two books for these two classes, was made, based on the lists of the Researchers in the field of thinking. Then it was submitted to a number of teaching staff at Tishreen University for arbitration, and arbitrated. The final list consisted of (17) skills and (40) indicators to these skills. The descriptive method was used. The tool consisted of a content analysis card, that was designed based on a list of basic thinking skills, to analyze the research sample consisting of science books for the first and second grades. The results of the research showed that the content contained (16) skill of the (17) skills of the basic thinking skills included in the list. Induction and observation skills were the most frequent compared with ordering, predicting and deduction skills which were the least frequent, In addition to not including the establishing criteria skill. The results also showed a lack of graduation in the ratios of including a number of skills such a comparison, description and representation. The researcher has, therefore, suggested including establishing criteria skill in Science curriculum’s content, taking into consideration the principle of graduation in the proportions of including some skills.